Urinary Neutrophil Gelatinase-Associated Lipocalin Can Predict the Efficacy of Volume Expansion Therapy in Patients With Hepatitis B Cirrhosis and AKI - Duan, Zhonghui; Jiang, Minjie; Huang, Xiaojie; Liu, Haixia; Yu, Hongwei; Meng, Qinghua (Frontiers in Pharmacology, 2022)
Abstract Backgrounds Kidney biomarkers in urine appear to be useful in differential diagnosis between Acute Tubular Necrosis (ATN) and other types of Acute kidney injury (AKI) in cirrhosis. In clinical practice, pre-renal azotemia (PRA) is often distinguished from other types of AKI by volume expansion therapy. Aim of the current study was to investigate the accuracy of urinary biomarkers in the differential diagnosis between PRA and other types of AKI. Methods A total of 65 patients with hepatitis B cirrhosis were prospectively included and divided into AKI and non-AKI groups. Patients with hepatitis B cirrhosis and AKI discontinue diuretics, vasodilators and nephrotoxic drugs and give volume expansion therapy. The efficacy was judged after 48 hours of treatment. Urinary biomarkers were measured at the time of diagnosis of AKI and 48 hours after volume expansion therapy. Univariate and multivariate analyses were used to identify independent risk factors for non-response to volume expansion therapy. Results Of the 65 patients, 49 patients with newly diagnosed AKI were screened in the study, and 16 hospitalized patients with hepatitis B cirrhosis without AKI at the same period were screened as the control group. In patients with cirrhosis and AKI, 29 (59.18%) patients were in the response group and 20 (40.81%) patients were in the non-response group. The mortality rate in the non-response group was significantly higher than that in the response group (75% VS 13.8% P<0.001). After Logistic regression analysis, urinary neutrophil gelatinase associated lipocalin (NGAL) (OR=1.000, 95% CI, 0.709-0.953, P<0.001) and serum creatinine (SCr) (OR=1.048, 95% CI: 0.697- 0.933, P<0.001) at diagnosis of AKI showed significant association with non-response to volume expansion therapy. The cut-off values for SCr and urinary NGAL were 128.50 umol/L and 90.75 ng/mL respectively. The area under the receiver operating curve (AUC) for SCr and urinary NGAL were 0.815 and 0.831. Conclusion Elevated urinary NGAL is an independent risk factor for non-response to volume expansion therapy. The levels of urinary NGAL in patients with cirrhosis prior to treatment can be used as a newly biomarker to distinguish PRA from ATN and HRS.